Effects of blood glucose level on 18F-FDG uptake for PET/CT in normal organs: A systematic review. - Clarice Sprinz; Stephan Altmayer; Matheus Zanon; Guilherme Watte; Klaus Irion; Edson Marchiori; Bruno Hochhegger (PLoS ONE)
Purpose To perform a systematic review of the effect of blood glucose levels on 2-Deoxy-2-[18F]fluoro-D-glucose (18F-FDG) uptake in normal organs. Methods We searched the MEDLINE, EMBASE and Cochrane databases through 22 April 2017 to identify all relevant studies using the keywords "PET/CT" (positron emission tomography/computed tomography), "standardized uptake value" (SUV), "glycemia," and "normal." Analysis followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses recommendations. Maximum and mean SUVs and glycemia were the main parameters analyzed. To objectively measure the magnitude of the association between glycemia and 18F-FDG uptake in different organs, we calculated the effect size (ES) and the coefficient of determination (R2) whenever possible. Results The literature search yielded 225 results, and 14 articles met the inclusion criteria; studies included a total of 2714 (range, 51-557) participants. The brain SUV was related significantly and inversely to glycemia (ES = 1.26; R2 0.16-0.58). Although the liver and mediastinal blood pool were significantly affected by glycemia, the magnitudes of these associations were small (ES = 0.24-0.59, R2 = 0.01-0.08) and negligible (R2 = 0.02), respectively. Lung, bone marrow, tumor, spleen, fat, bowel, and stomach 18F-FDG uptakes were not influenced by glycemia. Individual factors other than glycemia can also affect 18F-FDG uptake in different organs, and body mass index appears to be the most important of these factors. Conclusion The impact of glycemia on SUVs in most organs is either negligible or too small to be clinically significant. The brain SUV was the only value largely affected by glycemia.